L’impact de la pandémie sur les pratiques universitaires en didactique des langues - Widła, Halina (Neofilolog, 2022)
The article shares thoughts on the evolution of university practices under the influence of the pandemic. Although each university has its own training centre, the teaching offered has much in common, which means newly acquired experiences can be exchanged. We focus on applied foreign language studies. Integrating information and communication technologies in teaching centers the act of teaching on the learner. The question arises whether and to what extent we take into account the experiences of learners and teachers in the transmission of theoretical knowledge and cognitive skills. After 2 years of the COVID-19 pandemic, our research focused on appreciating the usefulness of teaching methods based on students’ experiences. We analyzed work conducted online by 37 philology students on pedagogical solutions in digital media. The research compared the students’ choice of types of exercises used to understand the content, consolidate knowledge, and carry out language correction. Theoretically, all these exercise types can be used for the same didactic purposes. However, the students’ preferences are reflected in the free choices they made. By evaluating these attempts by future teachers, on the basis of their typical choices and reactions, we facilitate and accelerate the training process.